The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.1159/000120842
|View full text |Cite
|
Sign up to set email alerts
|

Replacement La, inoplasty in Selective Dorsal Rhizotomy: Possible Protection against the Development of Musculoskeletal Pain

Abstract: The authors present a retrospective review of 35 patients who underwent selective dorsal rhizotomy between 1990 and 1992. The first 15 patients underwent laminectomy from L1 to the sacrum without replacement of the posterior elements. The subsequent 20 patients had the laminae replaced during wound closure. No patient in either group developed spinal instability or symptomatic deformity. However, 4 patients in the first group (mean follow-up period 35 months) developed significant low-back pain of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 13 publications
(22 reference statements)
0
15
0
Order By: Relevance
“…However, the authors would recommend such techniques to preserve the anatomical planes and thus facilitate potential future exposures [52]. In addition, a diminished degree of postoperative pain has been described in children with the use of laminoplasty techniques [53]. …”
Section: Discussionmentioning
confidence: 99%
“…However, the authors would recommend such techniques to preserve the anatomical planes and thus facilitate potential future exposures [52]. In addition, a diminished degree of postoperative pain has been described in children with the use of laminoplasty techniques [53]. …”
Section: Discussionmentioning
confidence: 99%
“…If back pain is considered a complication, only if it was severe enough to limit the usual activities of the patient, then 2.7% of the patients in this study had such a complication. Cobb et al [23], after reviewing a small series of SDR, suggested that delayed onset of back pain after SDR may be prevented by replacing the laminae at the end of the procedure. In this study, there were 4 cases of delayed back pain among 9 patients (44%) in whom the laminae were either not replaced or incompletely replaced, compared to 13 of 149 (9%) in whom the laminae were replaced.…”
Section: Back Painmentioning
confidence: 99%
“…Even if tumor recurrence or regrowth occurs postoperatively, taking a posterior approach remains as safe and easy as during the first operation because the dura mater is covered by the restored lamina [15][16][17]. Furthermore, other authors feel that osteoplastic laminectomy prevents the musculoskeletal pain observed after laminectomy [18].…”
Section: Discussionmentioning
confidence: 99%